2003
DOI: 10.1038/sj.onc.1206608
|View full text |Cite
|
Sign up to set email alerts
|

Role of the p38 MAPK pathway in cisplatin-based therapy

Abstract: p38 MAPK has been implicated in the response to cancer therapy. To determine whether the activation of p38 MAPK could be specific to cancer therapy, we investigated the activation of p38 MAPK in response to several chemotherapeutic agents, such as cisplatin, doxorubicin and taxol in several human cell lines. Activation of p38 MAPK was measured after exposure to several chemotherapeutic agents, using specific phosphoantibodies. Only cisplatin was able to activate p38 MAPK in all the cell lines tested. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(121 citation statements)
references
References 51 publications
13
108
0
Order By: Relevance
“…It is also known that p38 MAPK can be activated during different types of chemotherapy. Genotoxic drugs like cisplatin (Losa et al, 2003) as well as kinase inhibitors or ultraviolet and g-irradiation (Brancho et al, 2003;Losa et al, 2003) are recognized as agents able to stimulate p38 MAPK as well as JNK pathways (Bulavin et al, 1999;Sanchez-Prieto et al, 2000;Yu et al, 2000). It was reported that stimulation of p38 MAPK and JNK activity is crucial for cisplatin-induced apoptosis (Benhar et al, 2001), but specific inhibition of JNK or p38 MAPK suppresses the drug-induced cell death process (Tibbles and Woodgett, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that p38 MAPK can be activated during different types of chemotherapy. Genotoxic drugs like cisplatin (Losa et al, 2003) as well as kinase inhibitors or ultraviolet and g-irradiation (Brancho et al, 2003;Losa et al, 2003) are recognized as agents able to stimulate p38 MAPK as well as JNK pathways (Bulavin et al, 1999;Sanchez-Prieto et al, 2000;Yu et al, 2000). It was reported that stimulation of p38 MAPK and JNK activity is crucial for cisplatin-induced apoptosis (Benhar et al, 2001), but specific inhibition of JNK or p38 MAPK suppresses the drug-induced cell death process (Tibbles and Woodgett, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In A2780 ovarian carcinoma cells, ERK was weakly activated by cisplatin, whereas JNK was more significantly activated (Cui et al, 2000). In HaCaT cells, cisplatin did not activate ERK but did activate JNK and p38 MAPK (Losa et al, 2003). Chen et al reported that exogenous cannabinoids produced cellular protection by inactivation of JNK or p38 MAPK (Chen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the effects of PKCi on RhoB involved p38MAP kinase, U87MG cells depleted of PKCi were treated with the p38MAP kinase inhibitor SKF86002, which is active against all four p38MAP kinase members (Losa et al, 2003). SKF86002 had no effect on RhoB levels in U87MG cells, and did not affect the increase in RhoB with PKCi depletion (Figures 3c and d).…”
Section: Inhibition Of Pkci Activity Enhances Rhob Expressionmentioning
confidence: 99%